Netizen News Sources in the Journalistic Ethics Perspective (Case Study in Online Media Jogja.tribunnews.com) - nfn Winarni; Rani Dwi Lestari (BBPSDMP KOMINFO MAKASSAR, 2019)
The digital revolution has changed the practice of new media era journalism with a various journalistic display. One of them is the phenomenon of the use of Netizens' statement as a source of news on the news production in online media. The flaming of the development of the news cannot be separated from the influence of netizen opinion on giving comments or statements on an issue in the virtual realm. This study departs from the purpose of knowing how to use the statement of netizens as news sources on online media in a journalistic ethical perspective. This study uses a qualitative approach with a case study method. The results showed that the use of statement from netizens as a source of news was the process of producing news content on online media by taking netizen comments through observing the virtual world. From a journalistic ethics perspective, the use of the statement of netizens as a news source is not a violation as long as it fulfills the credibility and verification requirements. While in terms of credibility, it was found that some sources from netizens did not meet the credibility-standards of news sources.